2014
DOI: 10.18632/oncotarget.2640
|View full text |Cite
|
Sign up to set email alerts
|

The novel IκB kinase β inhibitor IMD-0560 prevents bone invasion by oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) cells display significantly augmented nuclear factor-κB (NF-κB) activity, and inhibiting this activity suppresses malignant tumor characteristics. Thus, we evaluated the effect of IMD-0560, a novel inhibitor of IκB kinase (IKK) β that is under assessment in a clinical trial of rheumatoid arthritis, on bone invasion by the mouse OSCC cell line SCCVII. We examined the inhibitory effects of IMD-0560 on NF-κB activity and tumor invasion using human OSCC cell lines and SCCVII cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Inhibition of the NF‐κB pathway has been suggested as a promising strategy for this malignancy . It has been documented that suppression of the NF‐κB activity via IMD‐0560, a novel inhibitor of IκB kinase β, blocks bone invasion by OSCC cells …”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Inhibition of the NF‐κB pathway has been suggested as a promising strategy for this malignancy . It has been documented that suppression of the NF‐κB activity via IMD‐0560, a novel inhibitor of IκB kinase β, blocks bone invasion by OSCC cells …”
Section: Introductionsupporting
confidence: 87%
“…NF‐κB activation involves phosphorylation and degradation of IκB, which releases NF‐κB from the inactivated complex and allows its nuclear translocation to transactivate target genes . Inhibition of the NF‐κB pathway has been suggested as a promising strategy for this malignancy . It has been documented that suppression of the NF‐κB activity via IMD‐0560, a novel inhibitor of IκB kinase β, blocks bone invasion by OSCC cells …”
Section: Introductionmentioning
confidence: 93%
“…IMD-0560 was shown to suppress TNF-␣-induced nuclear translocation of p65 and IB␣ degradation in OSCC cells and inhibit invasion of OSCC cells by suppressing MMP-9 production. IMD-0560 also prevented zygoma and mandible destruction by SCCVII cells, reduced the number of osteoclasts by inhibiting RANKL expression in osteoblastic cells and SCCVII cells, increased SCCVII cell death, and suppressed proliferation and MMP-9 production in SCCVII cells [68]. Based on these results, IMD-0560 may represent a new therapeutic agent to prevent bone invasion by OSCC ( Fig.…”
Section: The Effect Of Selective Nf-b Inhibitors On Bone Invasion By mentioning
confidence: 69%
“…Because genetic deletion of IKK␤ or p65 is lethal in embryonic mice, careful consideration should be given to the possibility that inhibition of NF-B may lead to severe side effects [27][28][29][30][31]. To address this point, we focused on the potential use of bortezomib, curcumin, or IMD-0560 to inhibit NF-B-driven bone invasion of OSCC in this review, because bortezomib is the only drug currently under clinical development, curcumin is a widely used food additive, and a phase I study of IMD-0560 has been completed without severe side effects [56][57][58][59][60][61][62]68]. In the case of mandibular bone invasion, where the tumor resides at the body's surface, it is possible to locally treat cancer with bortezomib, curcumin, or IMD-0560 and avoid any unexpected severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…We also revealed that these fibroblastic cells play crucial roles in OSCC‐associated osteoclastic bone resorption by producing IL‐6 and RANKL . Several groups have established animal models to explore the mechanism of bone destruction by OSCC in the jaw , and these models have been applied to investigate the effects of anti‐bone resorption agents such as bisphosphonates . However, in some experimental models, OSCC cells appeared to be in direct contact with the resorbing bone surface without the definite fibroblastic cell layer that is usually observed in human OSCC cases.…”
Section: Discussionmentioning
confidence: 95%